A repetitive DNA element regulates expression of the Helicobacter pylori sialic acid binding adhesin by a rheostat-like mechanism. - Anna Åberg; Pär Gideonsson; Anna Vallström; Annelie Olofsson; Carina Öhman; Lena Rakhimova; Thomas Borén; Lars Engstrand; Kristoffer Brännström; Anna Arnqvist (PLoS Pathogens, 2014)
During persistent infection, optimal expression of bacterial factors is required to match the ever-changing host environment. The gastric pathogen Helicobacter pylori has a large set of simple sequence repeats (SSR), which constitute contingency loci. Through a slipped strand mispairing mechanism, the SSRs generate heterogeneous populations that facilitate adaptation. Here, we present a model that explains, in molecular terms, how an intergenically located T-tract, via slipped strand mispairing, operates with a rheostat-like function, to fine-tune activity of the promoter that drives expression of the sialic acid binding adhesin, SabA. Using T-tract variants, in an isogenic strain background, we show that the length of the T-tract generates multiphasic output from the sabA promoter. Consequently, this alters the H. pylori binding to sialyl-Lewis x receptors on gastric mucosa. Fragment length analysis of post-infection isolated clones shows that the T-tract length is a highly variable feature in H. pylori. This mirrors the host-pathogen interplay, where the bacterium generates a set of clones from which the best-fit phenotypes are selected in the host. In silico and functional in vitro analyzes revealed that the length of the T-tract affects the local DNA structure and thereby binding of the RNA polymerase, through shifting of the axial alignment between the core promoter and UP-like elements. We identified additional genes in H. pylori, with T- or A-tracts positioned similar to that of sabA, and show that variations in the tract length likewise acted as rheostats to modulate cognate promoter output. Thus, we propose that this generally applicable mechanism, mediated by promoter-proximal SSRs, provides an alternative mechanism for transcriptional regulation in bacteria, such as H. pylori, which possesses a limited repertoire of classical trans-acting regulatory factors.